Assessment of the Microbiome and Potential Aflatoxin Associated With the Medicinal Herb Platycladus orientalis - Yu, Jingsheng; Guo, Mengyue; Jiang, Wenjun; Yang, Meihua; Pang, Xiaohui (Frontiers in Microbiology, 2020)
Platycladi Semen, which is derived from the dried ripe seed of Platycladus orientalis, has been used for the treatment of insomnia and constipation in China for 2000 years. However, it is susceptible to fungal and aflatoxin contamination under proper humidity and temperature during storage. Although aflatoxin contamination in Platycladi Semen has been reported preliminarily, few studies have been conducted on fungal infection and aflatoxin contamination simultaneously. Thus, this work aims to provide an in-depth understanding of fungal contamination in Platycladi Semen, and information on aflatoxin contamination. We focused on a comparison of the difference in fungal diversity between aflatoxin-contaminated and aflatoxin-free Platycladi Semen samples. First, aflatoxin levels in 11 Platycladi Semen samples, which were collected from local herbal markets in Shandong, Anhui, and Hebei provinces throughout China, were determined by IAC-HPLC-FLD, and positive confirmation of detected samples was performed by LC-MS/MS. The samples were divided into two groups, based on production or non-production of aflatoxin. We then used the Illumina MiSeq PE250 platform, and targeted the internal transcribed spacer 2 sequences to analyze the diversity and composition of the fungal microbiome, as well as to assess the presence of potential mycotoxin-producing fungi. Results showed that five samples were contaminated with aflatoxins, one of which exceeded the legal limits of Chinese Pharmacopoeia (2015). At the phylum level, the Ascomycota were the most dominant in all tested samples, with a relative abundance of 83.04%-99.46%. Aspergillus (27.88%-97.28%), Xerochrysium (0-28.49%), and Xeromyces (0-22.24%) were the three predominant genera. Furthermore, differences in fungal composition between the aflatoxin-contaminated and aflatoxin-free groups, as well as between different provinces were observed. A total of 74 species were identified, and four potential mycotoxin-producing fungi were detected in all samples, namely Aspergillus flavus, Aspergillus fumigatus, Fusarium poae, and Penicillium steckii. In conclusion, we report the great diversity of fungi associated with Platycladi Semen, highlight the risk to consumers of ingesting potent aflatoxin, and provide a reference for the safe application and quality improvement of Platycladi Semen.